The maternal brain and its plasticity in humans - Kim, Pilyoung; Strathearn, Lane; Swain, James E. (Hormones and behavior, 2016)
This article is part of a Special Issue “Parental Care”. Early mother–infant relationships play important roles in infants' optimal development. New mothers undergo neurobiological changes that support developing mother–infant relationships regardless of great individual differences in those relationships. In this article, we review the neural plasticity in human mothers' brains based on functional magnetic resonance imaging (fMRI) studies. First, we review the neural circuits that are involved in establishing and maintaining mother–infant relationships. Second, we discuss early postpartum factors (e.g., birth and feeding methods, hormones, and parental sensitivity) that are associated with individual differences in maternal brain neuroplasticity. Third, we discuss abnormal changes in the maternal brain related to psychopathology (i.e., postpartum depression, posttraumatic stress disorder, substance abuse) and potential brain remodeling associated with interventions. Last, we highlight potentially important future research directions to better understand normative changes in the maternal brain and risks for abnormal changes that may disrupt early mother–infant relationships. •Human maternal caregiving is governed by plastic brain networks.•The maternal brain networks integrate emotion and reward with cognitive control.•The human maternal brain adapts for mother–infant bonding.•The human maternal brain changes with psychopathology.•Parenting interventions may affect the plasticity of the human maternal brain.